Proceedings 2014 Network and Distributed System Security Symposium 2014
DOI: 10.14722/ndss.2014.23033
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Private File Retrieval by Combining ORAM and PIR

Abstract: Abstract-Recent research results on tree-based Oblivious RAM by Shi et al. [15] obtain communication complexity of O(l · log 3 (N )) in the worst-case for an N -capacity storage with blocks size l. The individual nodes in the tree, however, are constructed using traditional ORAMs which have worst-case communication complexity linear in their capacity and block size. PIR protocols are able to provide better worst-case bounds (decoupling capacity from block size), but have traditionally been less practical than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 11 publications
0
78
0
Order By: Relevance
“…Below, we briefly describe the original PIR protocol, and the protocols implemented by Mayberry et al [MBC13,MBC14]. In the following, assume a user want to recover a file among t files of bitsize s from a server.…”
Section: Applications To Pirmentioning
confidence: 99%
See 2 more Smart Citations
“…Below, we briefly describe the original PIR protocol, and the protocols implemented by Mayberry et al [MBC13,MBC14]. In the following, assume a user want to recover a file among t files of bitsize s from a server.…”
Section: Applications To Pirmentioning
confidence: 99%
“…Due to its conceptual simplicity and computational efficiency, this scheme was used as a building block of other PIR protocols [BPMÖ12,MBC13,MBC14,EÖM14], and to a private spectrum availability information retrieval protocol [GZL + 13]. In particular, it was implemented in Java by Mayberry et al [MBC13,MBC14] to demonstrate the practicality of PIR in a "real world" setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10]12,14]. These ORAMs only have little state information, such as secret keys and query counters, stored in local storage.…”
Section: Related Workmentioning
confidence: 99%
“…With such a storage arrangement, it has been shown that the communication cost for data query and shuffling is as low as log N data blocks per query. Compared to other state-of-the-art ORAM constructions [10,17,20], P-ORAM achieves higher communication efficiency.…”
Section: Introductionmentioning
confidence: 99%